2019
DOI: 10.1530/joe-18-0646
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone inhibits aneurysm formation and vascular inflammation in male mice

Abstract: Abdominal aortic aneurysm (AAA), one of the pathological phenotypes of vascular aging, is characterized by aortic dilation with impaired arterial wall integrity. Recent epidemiologic studies have shown that men with AAA have lower serum testosterone compared to men without. However, the underlying mechanisms remain unclear. In this study, we investigated the effects of testosterone on AAA formation using a murine AAA model under the conditions of depletion and administration of testosterone. In wild-type male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
12
0
4
Order By: Relevance
“…However, a recent case-control study comparing 65-year old men with and without AAA found that higher oestrogen, higher progesterone and lower testosterone levels were associated with AAA ( 170 ). The association of low testosterone levels with AAA is in line with an earlier clinical and murine study ( 70 , 77 ). This discrepancy in findings reflects the complexity of characterizing AAA development.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, a recent case-control study comparing 65-year old men with and without AAA found that higher oestrogen, higher progesterone and lower testosterone levels were associated with AAA ( 170 ). The association of low testosterone levels with AAA is in line with an earlier clinical and murine study ( 70 , 77 ). This discrepancy in findings reflects the complexity of characterizing AAA development.…”
Section: Discussionsupporting
confidence: 88%
“…Testosterone activates the androgen receptor, a transcription factor similar to the oestrogen receptors, that is expressed in many different cell types, including in vasculature and immune cells (66,67). While some researchers found that pharmacological blockade of the androgen receptor or deficiency of the receptor in male mice attenuated AAA formation (68) and castration of male mice with established AAA promoted aneurysm stabilization (69), others find the opposite (70). Also in humans there is controversy as to the beneficial or detrimental roles that testosterone (replacement therapy) plays in vascular disease (60,(71)(72)(73)(74).…”
Section: Sex Steroid Hormones: Oestrogen and Testosteronementioning
confidence: 99%
“…They found after 9-week testosterone administration, the aortic expression of IL-6 and IL-1β was decreased, and the dilated aortic diameter was also ameliorated, indicating the anti-inflammatory actions of testosterone administration on vascular pathologies. 31 In another animal study, the authors reported testosterone therapy improved lipid accumulation in rabbits that were fed fat-rich diets. A decrease in liver and plasma TNF-α was also observed in these rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, testosterone depletion and androgen receptor (AR) blockade precede AAA formation, and conversely, testosterone administration could suppress AAA formation by regulating macrophagemediated inflammatory responses. This anti-inflammatory action of testosterone/AR on AAA formation might provide a mechanistic insight into the vascular protective actions of testosterone and suggest that its proper administration or selective AR modulators might be novel therapeutic strategies for this aortic pathology [16].…”
Section: Pathophysiologymentioning
confidence: 91%